Climate-linked bonds - Dirk Broeders; Daniel Dimitrov; Niek Verhoeven (European Central Bank (ECB), 2025)
Climate-linked bonds, issued by governments and supranational organizations, are pivotal in advancing towards a net-zero economy. These bonds adjust their payoffs based on climate variables such as average temperature and greenhouse gas emissions, providing investors a hedge against long-term climate risks. They also signal government commitment to climate action and incentivize stronger policies. The price differential between climate-linked bonds and nominal bonds reflects market expectations of climate risks. This paper introduces a model of climate risk hedging and estimates that approximately three percent of government debt in major economies could be converted into climate-linked bonds.
Keywords: E58; G12; G13; Q54; 330; climate-linked bonds; climate risk; contingent claims; asset pricing; green finance